Transcriptomic Analysis Reveals Candidate Genes for Female Sterility in Pomegranate Flowers - Chen, Lina; Zhang, Jie; Li, Haoxian; Niu, Juan; Xue, Hui; Liu, Beibei; Wang, Qi; Luo, Xiang; Zhang, Fuhong; Zhao, Diguang; Cao, Shangyin (Frontiers in Plant Science, 2017)
Pomegranate has two types of flowers on the same plant: functional male flowers (FMF) and bisexual flowers (BF). BF are female-fertile flowers that can set fruits. FMF are female-sterile flowers that fail to set fruit and that eventually drop. The putative cause of pomegranate FMF female sterility is abnormal ovule development. However, the key stage at which the FMF pomegranate ovules become abnormal and the mechanism of regulation of pomegranate female sterility remain unknown. Here, we studied ovule development in FMF and BF, using scanning electron microscopy (SEM) to explore the key stage at which ovule development was terminated and then analyzed genes differentially expressed (differentially expressed genes - DEGs) between FMF and BF to investigate the mechanism responsible for pomegranate female sterility. Ovule development in FMF ceased following the formation of the inner integument primordium. The key stage for the termination of FMF ovule development was when the bud vertical diameter (BVD) was 5.0-13.0 mm. Candidate genes influencing ovule development may be crucial factors in pomegranate female sterility. INNER OUTER (INO/YABBY4) (Gglean016270) and AINTEGUMENTA (ANT) homolog genes (Gglean003340 and Gglean011480), which regulate the development of the integument, showed down-regulation in FMF at the key stage of ovule development cessation (ATNSII). Their upstream regulator genes, such as AGAMOUS-like (AG-like) (Gglean028014, Gglean026618, and Gglean028632) and SPOROCYTELESS (SPL) homolog genes (Gglean005812), also showed differential expression pattern between BF and FMF at this key stage. The differential expression of the ethylene response signal genes, ETR (ethylene-resistant) (Gglean022853) and ERF1/2 (ethylene-responsive factor) (Gglean022880), between FMF and BF indicated that ethylene signaling may also be an important factor in the development of pomegranate female sterility. The increase in BF observed after spraying with ethephon supported this interpretation. Results from qRT-PCR confirmed the findings of the transcriptomic analysis.